Pengaruh Motivasi Kerja, Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Badan Pusat Statistik (BPS) Brebes - Dwi Yoga; Andi Yulianto; Azizah Indriyani; Roby Setiadi; Nur Khojin (Journal of Economics and Management (JECMA), 2019)
In search of a good workforce is very not easy, especially in maintaining existing ones. Therefore, the company should prioritize employees who are skilled and have good performance. This research aims to determine the influence of work motivation, work environment and work discipline on the performance of employees at the Central Statistical Agency (BPS) Brebes. The study used primary data, a population of 35 employees and samples of 35 respondents. Hypothesis testing used multiple linear regression analyses using SPSS 16 applications. The results showed: partial work motivation has no significant effect on the performance of employees of the Central statistical Body (BPS) Brebes, the working environment partially influential to the performance of officers in the central body Brebes (BPS) statistics, partial work discipline has no significant effect on the performance of employees of the Central Statistical Board (BPS) of Brebes, and work motivation, work environment and working discipline simultaneously there are influences that to the performance of employees at the Brebes BPS.